Non-violent protests and civil societies in Nigeria, 1993-1999 (2012)
Non-violent methods of agitation for civic rights have been more successful in the 19th and 20th centuries than armed insurgencies and violent protests across the world. However, media and scholarship attentions have always focused on armed conflicts and unsuccessful non-violent protests. In Africa, there is a rich culture of non-violent agitations which not only contributes to preservation of lives but has successfully been used to transform societies. The study focuses on the non-violent methods adopted by democracy activists :o transit Nigeria from military dictatorship into democracy. The philosophical foundation, strategies, tactics, and methods of non- violent activities against military dictatorship are discussed. It is concluded that if the existing non-violent traditions and practices that helped in birthing democracy are nurtured, documented and disseminated appropriately among the population, they could sustain Nigerian extant fragile democracy and support the protection of civic rights of the people